2017
DOI: 10.1016/j.asoc.2017.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical genetic optimization of a fuzzy logic system for energy flows management in microgrids

Abstract: Bio-inspired algorithms like Genetic Algorithms and Fuzzy Inference Systems (FIS) are nowadays widely adopted as hybrid techniques in improving goods and services. In this paper we present an interesting application of the fuzzy-GA paradigm to the problem of energy flows management in microgrids, concerning the design, through a data driven synthesis procedure, of an Energy Management System (EMS). The main aim consists in performing decision making for power flow management tasks in the proposed microgrid mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…De Santis et al [107] introduced an energy management system for an interconnected MG using fuzzy logic based on the Mamdani algorithm. The main objective is to take decisions on the management tasks of the energy flow in the MG model, which is composed of renewable energy sources and energy storage elements.…”
Section: Energy Management Based On Artificial Intelligence Techniquesmentioning
confidence: 99%
“…De Santis et al [107] introduced an energy management system for an interconnected MG using fuzzy logic based on the Mamdani algorithm. The main objective is to take decisions on the management tasks of the energy flow in the MG model, which is composed of renewable energy sources and energy storage elements.…”
Section: Energy Management Based On Artificial Intelligence Techniquesmentioning
confidence: 99%
“…The literature presents only a few approaches that deal with intelligent decision-making to manage a power plant and the energy distribution [21].…”
Section: Related Workmentioning
confidence: 99%
“…Thirdly, many approaches simply react to the fluctuations of energy production and demand, without planning in advance [21,22]. Often their main goal has been an economical balance [21,23], and in some cases an energy balance has been considered [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the proposed multi-objective PSO could be validated for multi variable EMS of a factory. The optimal power control strategy for a standalone microgrid was developed and presented in [20] where optimized gains of a proportional-integrator controller of inverter-based DGs using hybrid big bang-big crunch (BB-BC) algorithm were found.With the aim of adjusting microgrid generation to energy demand, numerous technical studies have been carried out to improve energy management with penetration of renewable energy sources combined with energy storage devices in microgrids [21][22][23][24][25]. Alvarez et al [26] conducted an optimization of micro sources in a DG microgrid in terms of emission and fuel consumption costs.…”
mentioning
confidence: 99%
“…With the aim of adjusting microgrid generation to energy demand, numerous technical studies have been carried out to improve energy management with penetration of renewable energy sources combined with energy storage devices in microgrids [21][22][23][24][25]. Alvarez et al [26] conducted an optimization of micro sources in a DG microgrid in terms of emission and fuel consumption costs.…”
mentioning
confidence: 99%